Pollen season is reflected on symptom load for grass and birch pollen‐induced allergic rhinitis in different geographic areas—An EAACI Task Force Report. Issue 5 (1st March 2020) - Pfaar, Oliver; Karatzas, Kostas; Bastl, Katharina; Berger, Uwe; Buters, Jeroen; Darsow, Ulf; Demoly, Pascal; Durham, Stephen R.; Galán, Carmen; Gehrig, Regula; Gerth van Wijk, Roy; Jacobsen, Lars; et al.
Abstract: Background: The effectiveness of allergen immunotherapy (AIT) in seasonal and perennial allergic rhinitis (AR) depends on the definition of pollen exposure intensity or time period. We recently evaluated pollen and symptom data from Germany to examine the new definitions of the European Academy of Allergy and Clinical Immunology (EAACI) on pollen season and peak pollen period start and end. Now, we aim to confirm the feasibility of these definitions to properly mirror symptom loads for grass and birch pollen‐induced allergic rhinitis in other European geographical areas such as Austria, Finland and France, and therefore their suitability for AIT and clinical practice support. Methods: Data from twenty‐three pollen monitoring stations from three countries in Europe and for 3 years (2014‐2016) were used to investigate the correlation between birch and grass pollen concentrations during the birch and grass pollen season defined via the EAACI criteria, and total nasal symptom and medication scores as reported with the aid of the patient's hay‐fever diary (PHD). In addition, we conducted a statistical analysis, together with a graphical investigation, to reveal correlations and dependencies between the studied parameters. Results: The analysis demonstrated that the definitions of pollen season as well as peak pollen period start and end as proposed by the EAACI are correlated to pollen‐induced symptom loads reported by PHD users during birch and grass pollen season. A statistically significant correlation (slightly higher for birch) has been found between the Total Nasal Symptom and Medication Score (TNSMS) and the pollen concentration levels. Moreover, the maximum symptom levels occurred mostly within the peak pollen periods (PPP) following the EAACI criteria. Conclusions: Based on our analyses, we confirm the validity of the EAACI definitions on pollen season for both birch and grass and for a variety of geographical locations for the four European countries (including Germany from a previous publication) analyzed so far. On this basis, the use of the EAACI definitions is supported in future clinical trials on AIT as well as in daily routine for optimal patient care. Further evaluation of the EAACI criteria in other European regions is recommended.